Gereja Misioner: Sebuah Pembacaan Atas Arah Dasar Keuskupan Surabaya 2010-2019 - Berek, Yanuarius (Perspektif, 2014)
The source and purpose of mission as a unity is to participate in the mission of God (missio Dei). Participating in God’s mission means that mission is basically not the work of the Church but rather God’s action. God himself is the primary actor in mission itself. Within this mission concept this article tries to highlight mission dimensions of the local Church of the diocese of Surabaya. The diocese of Surabaya has formulated its vision as “Christ’s disciples who increasingly grow and become mature in faith, communion, service, and mission”. Formulating its vision in this way is surely assuming both a call to actively build communio within the Christian communities, namely the basic communities, as well as to reach out for missio The writer believes that both communion and mission are equally important aspects for being the Church of Christ.